Halal Critical Points and Consumer Trust in Halal Supply Chain Management: Evidence from a Traditional Tofu Factory in Indonesia - Firnanda Amalia Putri Herianti; Khoirun Nisak (Niqosiya: Journal of Economics and Business Research, 2026)
Although halal certification has become mandatory in Indonesia, many micro, small, and medium enterprises (MSMEs) have not formally implemented Halal Supply Chain Management (HSCM), creating challenges in ensuring halal integrity throughout the supply chain. Previous studies have mainly focused on HSCM implementation, with limited attention to halal critical points and stakeholder perceptions in relation to consumer trust. This study aims to analyze the implementation of HSCM at the Rembukidul Tofu Factory in Mojokerto Regency, identify halal critical points, examine stakeholder perceptions, and assess their implications for product quality and consumer trust. A qualitative case study approach was employed using semi-structured interviews with nine purposively selected informants and direct field observations. Data were analyzed based on four HSCM dimensions: halal procurement, halal manufacturing, halal distribution, and halal logistics, using the Halal Assurance System (HAS 23000) as the analytical framework. The findings indicate that HSCM implementation remains informal and does not fully comply with formal halal assurance standards. Three halal critical points were identified: the use of homemade fermented vinegar without laboratory verification, inadequate pest control, and the use of open containers during distribution. Despite these shortcomings, consumer trust remains strong, primarily driven by consistent product quality, long-term purchasing experience, and the factory's reputation rather than formal halal certification. This study contributes to the HSCM literature by highlighting the gap between informal halal practices and formal halal assurance while explaining how consumer trust is sustained in a community-based food MSME despite the absence of formal halal certification.